Women's Participation in Public Administration in Vietnam: A Case Study of Policy and Practice from 1986 to the Present. Issue 1 (2nd January 2022) - Nguyen, Dao
ABSTRACT: This paper highlights major trends in Vietnamese women's representation in public administration (PA) since 1986 and critically explains them within the framework of the gender mainstreaming policy. A systematic review of gendered documents indicates that women's participation in PA has improved over time. However, their representation in top leadership remains persistently low and fluctuates at all levels despite reinforced national machinery for gender equality (GE) and a series of enacted legislation and policies. Removing structural gender biases, relocating GE national machinery, and solving conflicts between gendered and PA legislation are key recommendations for bridging gaps between gendered quotas and reality.